2010
DOI: 10.1111/j.1539-6924.2010.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure Probability Under Parameter Uncertainty

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link: City Research OnlineElectronic copy available at: http://ssrn.com/abstract=1486317Electronic copy available at: http://ssrn.com/abstract=1486317Failure probability under parameter uncertainty * R. Gerrard A. Tsanakas † ‡ Cass Business School, City University LondonAbstract: In many problems of risk analysis, failure is equivalent to the event of a random risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 26 publications
(28 reference statements)
1
48
0
Order By: Relevance
“…The proof follows directly from the results in Gerrard and Tsanakas (2011), who show that P(Y ≤ VaR p [F µ,σ (·|X)]) = p, wherefrom the stated result is derived.…”
Section: Disentangling Parameter and Model Uncertaintymentioning
confidence: 68%
See 2 more Smart Citations
“…The proof follows directly from the results in Gerrard and Tsanakas (2011), who show that P(Y ≤ VaR p [F µ,σ (·|X)]) = p, wherefrom the stated result is derived.…”
Section: Disentangling Parameter and Model Uncertaintymentioning
confidence: 68%
“…The estimated capital is considered a random variable via its dependence on a random sample. Gerrard and Tsanakas (2011) investigate the changes in the probability of future losses exceeding capital, when the estimated capital is random due to parameter uncertainty. Bignozzi and Tsanakas (2015) quantify the impact of parameter uncertainty on risk measures beyond VaR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This question has already been raised in [11], where the authors showed that the probability of insolvency can be substantially higher than 0:5 % if the undertaking calculates its solvency risk capital without taking parameter uncertainty into account. As a consequence, the confidence level of 99.5 % required by Solvency II can only be achieved by a risk capital reflecting the parameter uncertainty.…”
Section: Introductionmentioning
confidence: 93%
“…Gerrard and Tsanakas [11] have applied this approach to parameter uncertainty for VaR-based solvency capital calculations. We discuss their results later in the paper.…”
Section: Introductionmentioning
confidence: 99%